2022
DOI: 10.1002/cjce.24428
|View full text |Cite
|
Sign up to set email alerts
|

Publication tips: How to write scientific articles that master the publication process and communicate your ideas efficiently

Abstract: This article gives insights on how to write, submit, revise, and publish articles in scientific peer-reviewed journals. I will focus on chemical engineering, but my suggestions apply to other natural sciences and engineering journals as well. I will start by discussing how to write the cover letter and the text of your article, emphasizing the importance of using clear language and highlighting the novelty of your results. I will then suggest how to prepare eye-catching figures and tables that communicate your… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…I have talked about some of these issues in two of my previous articles in the The Canadian Journal of Chemical Engineering (CJCE). [15,16] Lest you think that I am taking a holier-than-thou attitude, let me assure you that I have made these same blunders multiple times; it only takes a cursory look at my articles to realize that I have been guilty of the same sins that I mentioned above. It is hard to break away from these writing conventions because we are surrounded by technical literature written in the same flawed style.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I have talked about some of these issues in two of my previous articles in the The Canadian Journal of Chemical Engineering (CJCE). [15,16] Lest you think that I am taking a holier-than-thou attitude, let me assure you that I have made these same blunders multiple times; it only takes a cursory look at my articles to realize that I have been guilty of the same sins that I mentioned above. It is hard to break away from these writing conventions because we are surrounded by technical literature written in the same flawed style.…”
mentioning
confidence: 99%
“…I have talked about some of these issues in two of my previous articles in the The Canadian Journal of Chemical Engineering ( CJCE ). [ 15,16 ] If you know what these bad writing habits are, good; you are probably already writing articles that don't put your readers to sleep or throw them in dark pits of confusion. If you don't know what they are, you should be concerned; you can't avoid making these oversights if you are unaware of them.…”
mentioning
confidence: 99%
“…the CJCE and chemical engineering, [1] the future of chemical engineering, [2] and tips on how to master the scientific publication process and communicate your ideas efficiently. [3] The article written by Mehrotra et al [1] -A perspective on The Canadian Journal of Chemical Engineering commemorating its 100th volume: 1929-2021-tells of the changes that the CJCE has witnessed in our profession over the last 93 years. Figure 1 shows how the research topics in chemical engineering have evolved by contrasting bibliographic maps containing keywords from articles published in the CJCE from 1957-1979 and 2000-2021.…”
mentioning
confidence: 99%
“…I believe we must change the way we write our papers to make them more accessible, interesting, and rewarding for our readers. [3] On the technical side, this special issue includes 40 outstanding articles that cover the wide range of topics that define modern chemical engineering research, as shown in Figure 2.…”
mentioning
confidence: 99%